Development of DFM Enterprise car rental booking system / Julia Nasa Alus - Nasa Alus, Julia (2017)
The idea to develop this project rise after conducted an interview session with the stakeholder which is the owner of DFM Enterprise, Puan Azar Binti Aziz. The methodology used in completing this project is Waterfall Model. When each of the phases are finished, the problems are being solved as the objectives achieved. There are two type of booking system, which is stand-alone system and online booking system. The purpose of developing this system are to assist stakeholder in organize the information, to minimize the redundancy of booking and to assist in calculating the booking price. To solve the problem faced by the stakeholder, there are several objectives that need to be completed such as to gather and analyse requirement from stakeholder, to design and to develop the suggested system. As for this project the stand-alone system is more suitable compare to the online booking system. This is due to the limitation of stand-alone system. Therefore, by using it in this project, the limitation can be minimize. At the end of this project, the problems are being solved as the system can make booking and store the information of customers. Finally, there are several suggestions made as the recommendation for future works or improvements.